AN ANALYSIS OF LATENESS IN THE ADOPTION OF THE MINISTRY / INSTITUTIONAL BUDGET: Case Study on the Unit of Public Services Agency of the State Islamic University of North Sumatera North Medan - Muhammad Yafiz; Mailin Mailin; Bambang Lesmono (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
The purpose of this research is to find and analyze the factors that cause the delay in absorption of the budget of Ministries / Institutions, especially in the Public Service Agency Work Unit of the State Islamic University of North Sumatra, Medan. Data collection techniques used are documentation studies, interviews, and observations. The results showed that the budget realization at the State Islamic University of North Sumatra Medan in the first semester of the 2016-2019 fiscal year was still less than 40%. In 2016 the realization was 29.61% of the Budget Ceiling, in 2017 it decreased to 14.03% of the Budget Ceiling, in 2018 it was 16.58% of the Budget Ceiling and 2019 it was 26.20% of the Budget Ceiling. Of course, there will be an accumulation of budget absorption in the second semester or at the end of the year. From the research, it is concluded that the planning factors, human resource factors, and goods / services procurement factors influence the absorption of the budget at the Islamic State University of North Sumatra, Medan. To correct problems in planning factors, human resource factors and goods / services procurement factors, it is better if the State Islamic University of North Sumatra Medan reduces budget revisions and prepares the budget as accurately as possible according to the planned priority scale, transferring employees at the beginning of the fiscal year and proposing additional formation for the admission of Civil Servants or recruiting BLU honorary personnel who are competent in financial management and improving the quality of human resources by sending officials / employees to attend training and skills or training and increasing certified officials / employees for the procurement of goods / services. Keywords: Budget, absorption, planning, human resources, procurement.